1999
DOI: 10.1046/j.1439-0523.1999.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel source of resistance to angular leaf spot disease of common bean within the secondary gene pool

Abstract: Phaeoisariopsis griseola (Sacc.) Ferr., the agent of angular leaf spot disease of common bean, is a highly variable pathogen for which resistance gene diversification is required. This study analysed genetic resistance to this disease within genotypes of three Phaseolus species. Twenty‐nine genotypes of Phaseolus vulgaris, Phaseolus coccineus and Phaseolus polyanthus were inoculated with 54 isolates of Phaeoisariopsis griseola. The genetic resistance was estimated according to the symptom intensity observed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Recently, expanded evaluations reveal the secondary gene pool (P. coccineus and P. polyanthus) as an abundant source of resistance (Busogoro et al, 1999a;Mahuku et al, 2003). Mahuku et al (2003) identified 78 interspecific dry bean lines with resistance putatively transferred from the secondary gene pool, which represents important germplasm for future utilization.…”
Section: Angular Leaf Spotmentioning
confidence: 99%
“…Recently, expanded evaluations reveal the secondary gene pool (P. coccineus and P. polyanthus) as an abundant source of resistance (Busogoro et al, 1999a;Mahuku et al, 2003). Mahuku et al (2003) identified 78 interspecific dry bean lines with resistance putatively transferred from the secondary gene pool, which represents important germplasm for future utilization.…”
Section: Angular Leaf Spotmentioning
confidence: 99%
“…Hence, genetic resistance is the most cost-effective and environmentally friendly control measure at farm level (Busogoro et al, 1999;Odogwu et al, 2017). Broad resistance genes are generally bred into popular crop varieties, to protect them from new emerging pathogen races and prevent epidemics (Agrios, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Good sources of resistance have been found in such species as Phaseolus polyanthus Greenm. and Phaseolus coccineus L. (Busogoro et al 1999). The use of interspecific crosses in breeding is a promising tool for expanding the genetic base of the cultivated common bean and for overcoming some agronomical constraints (Broughton et al 2003).…”
Section: Introductionmentioning
confidence: 99%